Puesta en marcha de un proceso de gestión participativa de residuos plásticos hortícolas - Colonese, Maria Del Carmen; Bernardi, Maria Julia; Zoilo, Oscar Jose; Aguirre Estrada, Jose Maria; Sotelo, Mirian (Asociación Argentina de Horticultura (ASAHo), 2024)
Poster